Studies on Fruit and Yield Traits in Indigenous Coloured Varieties of Mango (Mangifera indica L.) in South Gujarat, India - H Rymbai (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2015)
An investigation on fruit descriptors and yield in twelve mango varieties was conducted under South Gujarat conditions. Maximum fruit length was recorded in cv. Totapuri (16.23cm). Vanraj showed the highest values for fruit width (11.67cm), fruit circumference (37.37cm), fruit weight (729g), fruit volume (575.59cm3) and fruit pulp (78.93%). Maximum TSS (21.20%), acidity (0.42%) and fruit firmness (7.00 rating) was observed in cvs. Deshi-1, Deshi-3 and Makaram, respectively. 'Totapuri' had maximum total shelf-life (21.33 days), number of fruits per tree (383.00) and fruit yield (236.80kg/tree). The varieties had green to yellow ground-colour of peel. All the varieties had red-blush peel colour, excepting cvs. Dadamio, Makaram and Swarnarekha which were purplish-red. Similarly, pulp colour ranged from light yellow to light orange. Based on overall performance, cvs. Alphonso, Deshi-1, Deshi-2, Kesar, Khandesi Borasio, Totapuri and Vanraj proved to be superior to the other varieties.